New Horizons in Counselor Pedagogy: The Intersection of Constructivist Concepts and Phenomenological Awareness. Issue 1 (April 2016) - WILKINSON, BRETT D.; HANNA, FRED J.
Abstract : This article explores how distinct epistemological assumptions in constructivism and phenomenology influence pedagogical approaches in counselor education. Ideological parallels akin to the humanist tradition are drawn, as are irreconcilable distinctions. Practical implications of each are discussed in relation to 3 important counselor training areas: theoretical orientation, psychological concepts, and self‐awareness.